Implikasi Artificial Intelligence Pada Aspek Perpajakan - Puji Rahayu (Universitas Trunojoyo Madura, 2024)
The presence of artificial intelligence (AI) has changed business practices and has had an impact on employment and professions. Meanwhile, the income received by workers and professionals is the object of income tax. If there is a decrease in labor revenue and professional service users, it may also be followed by a decrease in tax revenue from the income tax sector. The purpose of this study is to determine the implications of AI on taxation aspects. This research uses qualitative methods with descriptive data analysis. The results show that AI has a positive impact on making it easier for taxpayers to carry out tax obligations, improve tax services, detect tax fraud, and potentially increase tax revenue from the Income Tax Article (ITA) 17 (2), Value Added Tax (VAT), and ITA 23 sectors for delivery services. The negative impact of AI is a decrease in tax revenue from ITA 21 or ITA 23 for expert services, followed by a decrease in personal income tax for these experts and employees. Recommendations for domicile tax certificate (DGT) as a consideration for making policies related to income tax for the use of AI. In addition, as a consideration, it also makes regulations for the Ministry of Manpower to protect professional experts and labor, the Ministry of Communication and Information to protect AI user data, the Ministry of Education and Culture to protect the profession of educators and review the use of AI in education, IAI the education compartment as a consideration for planning a curriculum for accounting education to keep pace with technological developments or AI.